Identifikasi Faktor Perubahan Bidang Tanah dalam Lingkup Administrasi Pertanahan dengan Pendekatan Sistem Informasi Geografis - Rendra, Mrabawani Insan (Jurnal Kridatama Sains dan Teknologi, 2024)
This study aims to identify the factors influencing changes in land parcels related to land registration and land and building taxes. The methodology employed involves a spatial approach to changes in land parcels related to land administration, particularly land registration, and property taxes. The results indicated that the number of parcels changed is primary attributed to the division of joint rights, that used to known as "warinsan". furthermore, the factor of land use in residential areas exhibits the highest rate of change, accounting for 70%. The alteration of land parcels is primarily caused by the subdivision of land, constituting 72% of the cases, located proximately to village roads, lanes, or alleys